Efeito de gradientes de distúrbio na estruturação, composição e diversidade de interações de redes hospedeiro-parasitoide - Siqueira, Matheus Alves de (2024)
Landscape modifications resulting from the effects of fragmentation and habitat loss alter their physical structure and connectivity, influencing the availability and quality of resources, environmental factors, and the distribution patterns of local communities. In this context, the diversity of interactions established and the complexity of interaction networks between species are key factors for stability and ecosystem functions in these landscapes. Therefore, knowledge and understanding of the composition and organization of local communities and trophic interaction networks can be important tools for studies focused on the assessment, monitoring, development of strategies, and recovery of natural landscapes that have experienced or are experiencing anthropogenic disturbances or natural disruptions. Aiming to understand the impact of landscape alteration dynamics on community structure, this study aimed to estimate the abundance, species richness, complexity, and diversity of interaction networks in communities of parasitoid Hymenoptera and Lepidoptera on Croton floribundus (Euphorbiaceae) in areas with different gradients of preservation and disturbance, including: a Permanent Forest area, two areas with different restoration strategies (a Reforestation Area with natural processes and an Agro-silvopastoral System Area with anthropogenic processes), and an edge area between pasture and forest in restoration (non-restored area) at Fazenda Canchim, located in São Carlos – SP. Quantitative and descriptive analyses were used to estimate and compare biodiversity and species distribution in the four study areas, as well as the use of bipartite networks to study the structure, diversity, and organization of host-parasitoid interaction networks in the areas that compose the landscape as a whole.